2015
DOI: 10.1159/000430437
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic and Cerebellar Gray Matter Volume Reduction in Synthetic Cannabinoids Users

Abstract: Background: Synthetic cannabinoids are compounds that bind cannabinoid receptors with a high potency and have been used widely in Europe by young people. However, little is known about the pharmacology and morphological effects of this group of substances in the brain. This study is aimed at investigating the morphological differences among synthetic cannabinoids users and healthy controls. Methods: Voxel-based morphometry was used to investigate the differences in brain tissue composition in 20 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 15 publications
1
16
0
5
Order By: Relevance
“…Finally, we found that SUDs were associated with lower thalamic GM/WM across several substances including alcohol, cocaine, nicotine, methamphetamine, opioids and cannabis 55,56 . Reduced structural and functional integrity of the thalamus and its connectivity appear to be associated with the severity of SUD 57 .…”
Section: Primary Outcome: Altered Brain Morphometry In Sudsmentioning
confidence: 68%
“…Finally, we found that SUDs were associated with lower thalamic GM/WM across several substances including alcohol, cocaine, nicotine, methamphetamine, opioids and cannabis 55,56 . Reduced structural and functional integrity of the thalamus and its connectivity appear to be associated with the severity of SUD 57 .…”
Section: Primary Outcome: Altered Brain Morphometry In Sudsmentioning
confidence: 68%
“…SK'ların akut ve kronik dönemde psikomotor becerileri etkileyip etkilemediğini gösteren kontrollü çalışmalar henüz yeterli sayıda bulunmamaktadır. JWH-018, AM-2201, JWH-210, JWH-122 maruziyeti sonrası sürücülük becerilerinin ölçüldüğü bir çalışmada SK' kullanıcılarının sağlıklı kontrollere göre psikomotor becerilerinin daha düşük olduğu saptanmış olup, çalışmadaki örneklem sayısı sonuçların genellenebilirliği için oldukça düşüktür 27 Baş dönmesi 77 Kronik SSS'de yapısal ve işlevsel bozumlara ait bulgular 42,56 Hipokampus ve amigdalada yapısal ve işlevsel değişiklikler 53,54 saptanmıştır 28 . Sürücüler ile yapılan başka bir çalışmaya göre de bir SK türevi olan UR-144'ün esrara göre psikomotor becerileri ve sürücü performansını daha olumsuz etkilediği bildirilmiştir 29 .…”
Section: Psikomotor Becerilerunclassified
“…Bu çalışma SK kullanıcılarının bu alanda sıkıntı yaşadıklarını göstermektedir. Görsel ve işitsel seçici dikkatte gerekli olmayan arka plan uyaranlarını inhibe etmekte görevli talamusun gri cevherinde (CB1 reseptörlerince zengin) uzun süreli SK kullanıcılarında incelme tespit edilmiştir42 . SK kullanıcılarında, CB1 Arşiv Kaynak Tarama Dergisi .…”
unclassified
See 1 more Smart Citation
“…Furthermore, loss of gray matter volume has been described in the cerebellum of cocaine addicts (Sim et al, 2007;Moreno-Lopez et al, 2015), cannabis smokers (Battistella et al, 2014;Nurmedov et al, 2015), heroin addicts (Lin et al, 2012) and alcoholics (Durazzo et al, 2015;Sawyer et al, 2016), paralleling prior observations in the striato-cortico-limbic networks (Fein et al, 2002;Matochik et al, 2005;Kim et al, 2006;Sim et al, 2007).…”
Section: The Involvement Of the Cerebellum In Drug-induced Cue Reactimentioning
confidence: 56%